Hubungan Dukungan Keluarga dengan Kepatuhan Pembatasan Cairan pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di Rs. Sentra Medika Minahasa Utara - Pongantung, Edelina; Masi, Gresty Natalia Maria; Fitriani, Fitriani (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background Adherence to fluid intake restrictions is a necessary part of therapy for hemodialysis patients in order to maintain the balance between fluid intake and output. However, many hemodialysis patients fail to comply with these restrictions. This non-adherence poses a significant problem, as it can negatively affect the patient’s condition. Family support is one of the key factors that plays an important role in encouraging patient adherence to therapy. With optimal support from family members, patients are more likely to comply with the recommended treatment or therapeutic process. Objective This study aims to examine the relationship between family support and adherence to fluid restriction among CKD patients undergoing hemodialysis at Sentra Medika Hospital, North Minahasa. Methods A quantitative study was conducted using a cross-sectional design. A total of 143 respondents were selected through purposive sampling. Data were collected using a family support questionnaire and a fluid restriction adherence questionnaire. Statistical analysis was performed using the Gamma correlation test. Results The results indicated that the majority of respondents reported a moderate level of family support (62.94%) and low adherence to fluid restriction (84.6%). The Gamma correlation test revealed a significant relationship between family support and adherence to fluid restriction (p = 0.000). Conclusion There is a statistically significant relationship between family support and adherence to fluid restriction in CKD patients undergoing hemodialysis. Keywords: Chronic kidney disease, family support, fluid restriction adherence, hemodialysis